Traffic problems in Southeast Asia featuring the case of Cambodia's traffic accidents involving motorcycles. (December 2018) - Kitamura, Yuto; Hayashi, Makiko; Yagi, Eriko
Abstract: This article provides the background to the special issue by reviewing the status of traffic problems in South East Asian countries, and in particular, the case of Cambodia. The "Make Roads Safe" report by the Commission for Global Road Safety (2011) confirms traffic accidents as the primary cause of youth mortality worldwide. Thus, theUnited Nations declared the decade from 2011 to 2020 as the "UN Decade of Action for Road Safety 2011-2020", promoting road safety and to reduce the number of deaths in road accidents by 2020. Furthermore, the "Sustainable Development Goals" adopted in 2015 highlight the important role of sustainable transport in tackling the exclusion of vulnerable groups. On the other hand, theWorld Health Organization in 2015 indicate an increase in the death rate due to traffic accidents in low-income countries since 2000. Traffic accidents were already recognized as a social problem before the 2000s in countries such as Thailand and the Philippines. At the same time, other ASEAN member states such as Vietnam and Cambodia which have experienced rapid economic growth since the 2000s are now experiencing the seriousness of traffic problems. It is said that 70% of road accidents in Thailand, Cambodia and Laos involve motorcycles and three-wheelers, but despite this situation, the regulatory framework for motorcycles remains undeveloped. In the case of Cambodia, speeding by young people remains the major cause of road deaths and this can be explained by the fact that people can now travel at a higher speed because of road developments but remaining challenges related to underdeveloped traffic legislation, and limited public awareness and knowledge of road safety are overlooked. In 2010, the Cambodian National Road Safety Action Plan 2010–2020 was drafted, aiming to halve the number of deaths in traffic accidents in 2020. However, in reality, the number of road deaths did not decrease to the level anticipated in the action plan until 2016. In this article, the authors emphasize the importance of implementing the "three Es" namely Engineering, Enforcement and Education in developing countries such as Cambodia. In particular, the authors claim that the role of education to increase people's road safety awareness is neglected compared to the other two dimensions and thus, it is highly important to raise people's road safety awareness through education among the young people. Highlights: Seventy-four percent of road traffic accidents in the world take place in low income countries. In particular, the number of accidents in Southeast Asian countries has been rapidly increasing in recent times. The penetration rate of two-wheeled vehicles (motorcycles) in Southeast Asian countries is very high in a global context. Since the 2000s, the number of traffic accidents in Cambodia has been rising and in particular, the number of accidents involving motorcycles driven by young people is high. '